Empowering Women through Entrepreneurship Education: A Pathway to Economic Prosperity in Indonesia - Djati, Astrid Laksmita; Putri, Meylisa Eka; Andriyani; Ratnawati, Intan (LifeSciFi, 2024)
Gender equality is an important focus to discuss as the basis of the global movement for women's empowerment. To achieve economic prosperity in Indonesia, one of the women empowerment programs that can be implemented is the provision of entrepreneurship education. With an emphasis on innovation and skill development, this study highlights how entrepreneurship education not only creates better job opportunities, but also significantly improves women's competitiveness in the workforce. It is therefore necessary to explore the relationship between entrepreneurship education and women's empowerment in the context of sustainable economic prosperity in Indonesia. This study uses the Systematic Literature Review (SLR) method through the Watase Uake website. Data was obtained through analysis of relevant articles from reputable journals. The analysis shows that entrepreneurship education helps women develop the skills needed to manage businesses, understand finances and respond to market changes, contributing to financial independence and family well-being. The findings of this study are that entrepreneurship education has a significant role in increasing women's participation in sustainable economic sectors and positively impacting national economic growth through greater empowerment of women in sustainable and environmentally friendly economic activities. Through women's economic empowerment, it is hoped that community welfare can be achieved more equitably, fairly and sustainably in the long term.